How Servant Leadership Leads to Employees’ Customer-Oriented Behavior in the Service Industry? A Dual-Mechanism Model - Yuan, Mengru (Int J Environ Res Public Health, 2020)
Although servant leadership has been acknowledged as an important predictor of employees’ behavioral outcomes in the service industry, there is still no cohesive understanding of the positive association between servant leadership and employees’ customer-oriented behavior (COB). This research, drawing on cognitive affective processing system theory (CAPS), empirically investigates the influence of servant leadership on employees’ COB by exploring two mediators (i.e., organizational identification and vitality). We conducted two studies in China, using a cross-sectional design to survey employees in service-oriented technical organizations (Study 1) and a time-lagged design to survey hospitality employees with frontline service jobs in star-level hotels (Study 2). Across both samples, we found that servant leadership enhanced employees’ COB by simultaneously increasing their organizational identification and vitality. We discuss the implications of these results for future research and practice.